2017
DOI: 10.1590/1806-9282.63.02.156
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia and its relation with chronic low-grade inflammation in obesity

Abstract: Oliveira arS et al. 156rEv assoc mEd Bras 2017; 63(2):156-163

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
1
18
0
4
Order By: Relevance
“…Some studies reported that dietary intake of magnesium is inversely related to physiometric measures such as BMI, waist circumference, and body fat composition [33,34]. Hypomagnesemia also leads to decreased antioxidant enzyme activities, with concomitant increased production of damaging reactive oxygen species (ROS) by inflammatory cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that dietary intake of magnesium is inversely related to physiometric measures such as BMI, waist circumference, and body fat composition [33,34]. Hypomagnesemia also leads to decreased antioxidant enzyme activities, with concomitant increased production of damaging reactive oxygen species (ROS) by inflammatory cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, magnesium’s role as a calcium antagonist may be important. Prolonged opening of calcium channels and activation of N-methyl-D-aspartate (NMDA) receptors in the absence of magnesium leads to a cascade of events, which favor the inflammatory process [ 35 ]. In the presence of increased concentrations of intracellular calcium, phagocytic cells are activated leading to increased cytokine production [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficiencies have been reported frequently in obesity [90][91][92][93][94][95][96][97][98][99][100][101]. Different causal factors between obesity and hypomagnesemia have been suggested.…”
Section: Low Magnesium Levels Are Often Seen In Obesitymentioning
confidence: 99%